Розвиток психологічної ресурсності у процесі служби в поліції - Олексин, М. О.; Oleksyn, M. O. (Габітус. - 2023. - Вип. 52. - С. 249-253, 2023)
У статті досліджено процес розвитку психологічної ресурсності у працівників поліції під час їх професійної служби. Поліцейська служба є високостресовою професією, яка вимагає стресостійкості й адаптації до непередбачуваних ситуацій. Значущі ризики професійного вигорання та негативного впливу стресу на психічний стан актуалізують дослідження, спрямовані на вивчення процесу розвитку психологічної ресурсності в контексті професійного зростання поліцейських. Виявлено особливості формування психологічної ресурсності в поліцейських із різним досвідом служби, а також проаналізовано вплив професійних переживань і стресових ситуацій на її динаміку.

This article examines the process of developing psychological resourcefulness in police officers during their professional service. The police service is a highly stressful profession that requires high stress resistance and adaptation to unpredictable situations. Taking into account the significant risks of professional burnout and the negative impact of stress on the mental state, this study is aimed at studying the process of developing psychological resourcefulness in the context of the professional growth of police officers. In modern society, policing plays a key role in maintaining public order, ensuring security and preventing crime. Professional service in the police involves high responsibility, inevitable interaction with conflict and stressful situations, as well as constant susceptibility to psychological stress and traumatic events. In this regard, the ability of police officers to effectively cope with various professional challenges and stressful situations plays a decisive role in their professional success, as well as in their physical and mental well-being. One of the key aspects determining the successful performance of professional duties is the psychological resourcefulness of police officers. Psychological resourcefulness is a complex of psychological qualities and mechanisms that contribute to adaptation and overcoming difficulties associated with professional activity. This resource allows police officers to maintain a level of stress resistance, emotional stability, positive thinking and psychological well-being in a complex and dynamic service environment. Despite the importance of psychological resourcefulness for police officers, the process of its development and its specifics in the context of police service remain poorly studied. Understanding the factors contributing to the development of psychological resourcefulness in police officers, as well as identifying its dynamics at various stages of a professional career, is important for the development of targeted programs and measures aimed at supporting and strengthening the psychological well-being of police officers. The purpose of this scientific article is to study the process of developing psychological resourcefulness in police officers during their service. We aim to reveal the peculiarities of the formation of psychological resourcefulness in police officers with different service experience, as well as to analyze the influence of professional experiences and stressful situations on its dynamics. This article has important practical implications for psychologists, law enforcement professionals, and all stakeholders involved in supporting and enhancing the psychological well-being of police officers. We hope that the results of our research contribute to increasing the efficiency of the work of law enforcement agencies, ensuring safety and caring for the professional interests and mental health of police officers.

Исследован процесс развития психологической ресурсности у работников полиции во время их профессиональной службы. Полицейская служба является высокострессовой профессией, которая требует стрессоустойчивости и адаптации к непредсказуемым ситуациям. Выявлены особенности формирования психологической ресурсности у полицейских разным опытом службы, а также проанализировано влияние профессиональных переживаний и стрессовых ситуаций на ее динамику.
Development of psychological resources in the process of service in the police
Keywords: психологічна ресурсність; psychological resourcefulness; психологическая ресурсность; працівники поліції; police officers; работники полиции; морально-психологічна готовність; moral and psychological readiness; морально-психологическая готовность; професійна діяльність; professional activity; профессиональная деятельность